2016
DOI: 10.7861/clinmedicine.16-5-481
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions

Abstract: Adverse drug reactions (ADRs) remain a challenge in modern healthcare, particularly given the increasing complexity of therapeutics, an ageing population and rising multimorbidity. This article summarises some of the key facts about ADRs and explores aspects relating to their prevention, diagnosis, reporting and management in current clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
158
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(197 citation statements)
references
References 16 publications
(13 reference statements)
1
158
0
3
Order By: Relevance
“…There may be various explanations for differences in ADR rates between studies including differences in data collection methods and ADR definitions. In general, however, the numbers indicate a point of concern since ADRs may be bothersome and may reduce treatment adherence, efficacy, quality of life and increase healthcare costs …”
Section: Introductionmentioning
confidence: 99%
“…There may be various explanations for differences in ADR rates between studies including differences in data collection methods and ADR definitions. In general, however, the numbers indicate a point of concern since ADRs may be bothersome and may reduce treatment adherence, efficacy, quality of life and increase healthcare costs …”
Section: Introductionmentioning
confidence: 99%
“…On the other side of the Atlantic Ocean, in Sweden, fatal ADRs were estimated as a comparable public health burden, the seventh most common cause of death (Wester et al, 2008). Studies undertaken on drug safety over the past three decades have collectively shown that ADRs are common in clinical practice, occurring in about 5-10% of patients and resulting in unscheduled hospitalizations, or occurring during hospital stay or after discharge from the hospital (Coleman and Pontefract, 2016). It is important to note that ADRs are often underreported in clinical practice.…”
Section: Why Personalized Medicine? Why Now?mentioning
confidence: 99%
“…When identifying uses of the concept, seven articles defined adverse reaction to medications as effects or events associated to any situation involving medication use (Alhawassi, Krass, Bajorek, & Pont, ; Chen et al., ; Coleman & Pontefract, ; Ho, Le, Thai, & Taewijit, ; Muringazuva et al., ; Riedl & Casillas, ; Wooten, ). Three defined it as reactions that occur with the proper use of a medication and standard doses (Asscher, Parr, & Whitmarsh, ; Su, Chung, & Hung, ; Vervloet & Durham, ).…”
Section: Evaluation Of Findingsmentioning
confidence: 99%
“…In the present study, antecedents for adverse reaction to medications were identified in 29 articles (Table ). On the other hand, consequences are outcomes of the concept, such as quality of life impairment, economic impact, death, hospital admission, and morbidity (Chen et al., ; Coleman & Pontefract, ; Onder et al., ; Su et al., ). Clinical manifestations can also be experienced, for example, acute renal failure, hypotension, arrhythmia, cutaneous reaction, gastrointestinal complaints, falls, electrolyte disorder, anemia, infections, and bleeding (Alsbou et al., ; Coleman & Pontefract, ; Davies et al., ; Muñoz‐Torrero et al., ; O'Connor, Gallagher, Byrne, & O'Mahony, ; Onder et al., ; Passarelli, Jacob‐Filho, & Figueras, ; Rashed et al., ; Shah et al., ; Smyth et al., ).…”
Section: Evaluation Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation